2017
DOI: 10.1155/2017/6803682
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis Crisis Associated with Thyrotoxicosis due to Graves’ Disease

Abstract: We present the case of a patient with previous psychiatric illness, acutely exacerbated by thyroid storm due to Graves' disease, in whom treatment with antipsychotics induced catatonia. These associations are extremely rare and may be confused with Hashimoto's encephalopathy, especially in the presence of anti-thyroid antibodies in cerebrospinal fluid. The treatment consists in the control of the triggering disease (in this case the resolution of the thyrotoxicosis) and the use of benzodiazepines. However, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It is not uncommon for individuals with Graves' disease and other forms of thyrotoxicosis to display subtle neuropsychiatric abnormalities such as irritability, anxiety, sleep disturbances, confusion, mood changes, and memory deficits [ 4 ]. In the United States, thyrotoxicosis affects 1.2% of the population, with 0.5% overt cases and 0.7% subclinical cases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not uncommon for individuals with Graves' disease and other forms of thyrotoxicosis to display subtle neuropsychiatric abnormalities such as irritability, anxiety, sleep disturbances, confusion, mood changes, and memory deficits [ 4 ]. In the United States, thyrotoxicosis affects 1.2% of the population, with 0.5% overt cases and 0.7% subclinical cases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, psychiatric manifestations were predominantly linked to hypothyroidism. However, emerging research has revealed that hyperthyroidism, characterized by an excess of thyroid hormones, can also lead to a wide range of psychiatric symptoms [ 3 , 4 ]. Patients with thyrotoxicosis, the state of excessive thyroid hormone production, may exhibit symptoms such as anxiety, restlessness, emotional lability, depression, mania, and, in rare cases, acute psychosis, paranoia, and schizophreniform features [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychosis can be managed with the administration of antipsychotic agents [ 8 ]. However, caution should be maintained as treatment with antipsychotics may lead to catatonia [ 9 ]. In addition, mood stabilizers and antidepressant can be used for better control of symptoms [ 8 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…82,83 Dietary vitamin B12 deficiency might also cause catatonia. 84,85 In thyroid disease, catatonia has been reported in patients with thyroid autoantibodies with hyper thyroid, [86][87][88] hypothyroid, 90,91 and euthyroid 91,92 states. However, catatonia has also occurred in hypothyroidism due to thyroidectomy; 93 whether thyroid status or the presence of the autoantibodies is the causally relevant factor therefore remains unclear.…”
Section: Autoimmune Disorders Causing Catatoniamentioning
confidence: 99%